Macroeconomic Factors and Market Indicators Affecting Islamic Mortgage Financing in Indonesia - Putri, Diana Clarisa Alya; Laila, Nisful (Universitas Airlangga, 2025)
This study aims to analyze the influence of the BI Rate, Gross Domestic Product (GDP), Residential Property Price Index (RPPI), and Indonesia Sharia Stock Index (ISSI) on the mortgage financing of Islamic banks in Indonesia. The objective of this research is to provide recommendations for the government in formulating macroeconomic policies that facilitate public access to Islamic mortgage financing. This research employs a quantitative approach using the Autoregressive Distributed Lag (ARDL) method, processed with E-Views 12. Data were sourced from Islamic Banking Statistics by OJK, Bank Indonesia, Kemendagri, BPS, and CEIC for the 2014-2024 period. The findings indicate that in the short term, the BI Rate and GDP have a significant positive influence, while RPPI has a significant negative influence on Islamic mortgage financing. Conversely, ISSI shows no significant influence in the short term. In the long term, only GDP has a significant positive impact on Islamic mortgage financing, whereas the BI Rate, RPPI, and ISSI exhibit no significant effects. These findings provide critical insights into the dynamics of macroeconomic variables affecting Islamic mortgage financing and their implications for economic policy formulation.